Dokumentasi Arsitektural Bangunan Museum Balee Juang Kota Langsa - Liana, Indah; Karsono, Bambang; Olivia, Sisca (Departemen Arsitektur Fakultas Teknik Universitas Brawijaya, Indonesia, 2024)
Balee Juang Museum is a Dutch colonial heritage building located in Kota Langsa District, Aceh Province. This building was built by the Dutch and became one of the historical buildings. The building has undergone a change of use since the 1920s until now. The purpose of this study is to measure and compile digital documentation in the form of Computer-Aided Design and Drafting (CADD) and 3D modeling. This study applies a hybrid method between analog and digital by applying technology according to the target data based on guidelines from the Historic American Buildings Survey (HABS). The observations are presented in the form of informative and measurable descriptive digital documents regarding the Balee Juang Building in Langsa City.